The Labor Force, Foreign Investment (FI), and Domestic Investment (DI) on Economic Growth in North Sumatra Province from 2011 to 2023 - Tohonan Rohani; Ujianto (Journal of Business Management, 2025)
This research analyzes the influence of the Number of Workforce, Foreign Direct Investment (FDI), and Domestic Investment (DI) on the economic growth of North Sumatra Province during the period 2011–2023. Economic growth is measured using Gross Regional Domestic Product (GRDP) at constant prices. Secondary data from the Central Statistics Agency (BPS) and the Investment Coordinating Board (BKPM) are analyzed using multiple linear regression with natural logarithm transformation. The results indicate that, collectively, the three variables have a significant effect on economic growth. Partially, Domestic Investment (DI) has a positive and significant impact, whereas Foreign Direct Investment (FDI) and the Number of Workforce do not show significant effects. These findings emphasize the importance of domestic investors and highlight the need for improving workforce quality and more effective management of foreign investments. Further research is recommended to include additional variables such as infrastructure, government expenditure, or technology to provide a more comprehensive analysis